Introduction to academic writing Level 3 - Oshima, Alice; Houge, Ann (White Plains, NY Pearson Education, 2007)
Introduction to Academic Writing helps students to master the standard organizational patterns of the paragraph and the basic concepts of essay writing. It integrates the study of rhetorical patterns and the writing process with extensive practice in sentence structure and mechanics.
Keywords: Ngôn ngữ Anh